Instalação de coroas implantadas distais para modificação da classificação de pacientes classe I para classe III de Kennedy - Zancopé, Karla (2014)
The teeth loss causes disharmony in the stomatognathic system, especially when it occurs bilaterally in the posterior mandible. In these cases, free-end removable partial dentures (FERPD) are the most widely used, because it has low cost and do not require any surgical procedures. However, this type of prosthesis have the worst prognosis, since there is an intrusion movement of the FERPD into the ridge and mouth floor that occurs during mastication. To solve this problem, since the early 90\'s it has been proposed the insertion of an implant in the extreme posterior region of the mandible serving as a stop for the FERPD. However, the literature review does not describe what is the best abutment recommended in this case; nor what is the impact of the treatment proposed for the RPD abutment tooth. The aim of this study was to evaluate the impact of the placement of distal implants to support or retain a FERPD in Kennedy class I patients. First, a systematic review on the subject was performed to evaluate the recent literature. Second, a photoelastic study to evaluate patterns of stress distribution around the implant and abutment tooth to analyze the influence of the implant connection type (internal or external) and the prosthetic implant device (crown or attachment) to support a RPD. Finally, the stress distribution were evaluated around the abutment tooth and in different sizes of implants to support a FERPD associated with a metallic crown, using the Finit Element Analysis. According to the results obtained in the present study, it was concluded that the analyzed treatment benefits the patients satisfaction and chewing ability, without decreasing the survival rate of implants; metallic crowns associated with Morse taper implants demonstrated better biomechanical behavior. Shorter length of the implant did not alter the patern of stress. There is still a lack of clinical studies on the use of distal implants associated with a FERPD, considering the survival rate of the abutment teeth.